Governance, Gross Capital Formation, Foreign Remittances and Economic Growth in Zimbabwe - Maune, Alexander; Matanda, Ephraim; Chitombo, Ezekiel (Acta Universitatis Danubius. Œconomica, 2023)
Purpose: This article examined the impact of governance, gross capital formation, and foreign remittances on economic growth in Zimbabwe between 1996 and 2021. Approach: The study pursued a deductive approach to collect and analyse data secondary data collected from World Bank Development Indicators. The study used a multiple linear regression model to examine the data. Data were collected from 1996 to 2021. Findings: The regression coefficients depicted a direct relationship between the dependent variable and the three independent variables. The study findings also revealed that governance has the highest contribution to Zimbabwe’s gross domestic product compared to the other two independent variables in the period under review. The coefficients of determination of the independent variables, R2 to Zimbabwe’s gross domestic product are 0.6876, 0.5274 and 0.4876 respectively. Practical implications: This study has practical implications for policy formulation and implementation as well as for further future research in Zimbabwe given the important role of governance, gross capital formation and foreign remittances on economic growth. Importantly, these are policies that attract foreign remittances as well as encourage good governance and gross capital formation in the country. Foreign remittances have become a huge source of foreign currency in the last decades in Zimbabwe. Originality/value: Literature has shown a lack of consensus regarding the impact of governance, gross capital formation, and foreign remittances on economic growth thereby creating some knowledge gaps in the field, particularly in developing countries. This article, therefore, seeks to close this gap by looking at the impact of the three variables on economic growth in Zimbabwe from 1996 to 2021.